Pengaruh Tambahan Penghasilan Pegawai (TPP) terhadap Kinerja Aparatur Sipil Negara (ASN) pada BPKAD Kabupaten Lombok Barat - Rosyia Wardani; Baiq Ertin Helmida; Baiq Soehartini (Target : Jurnal Manajemen Bisnis, 2023)
This study aims to determine: the application of TPP (additional employee income) and ASN performance at BPKAD West Lombok Regency, as well as the effect of TPP implementation on ASN performance at BPKAD West Lombok Regency. The type of research used in this research is descriptive and associative. The population in this study were all ASN employees at BPKAD West Lombok Regency, totaling 59 employees. The number of samples used was 58 employees with purposive sampling method. The data analysis technique used is descriptive, classic assumption test and simple linear regression. The results showed that the implementation of TPP in the West Lombok BPKAD in terms of Class of Position, Workload and Attendance was in the "Good" category (average 4.09); The ASN's performance at the West Lombok BPKAD was in the "Good" category (4.03). The results of simple linear regression analysis obtained the equation Y = 26.536 + 0.266X and from the results of the hypothesis test the value of t count > t table (4.548 > 1.6715) showed that TPP had an effect on ASN performance at BPKAD Lombok Barat.